Inspiratif (comprehensive stunting prevention initiative): Specific stunting intervention efforts in Pangkajene Kepulauan District - Suni Hariati; Erfina Erfina; Nur Fadilah; Andi Dwi Bahagia; Nurmaulid Nurmaulid; Muh. Imanuddin Taqwa Karim (Universitas Muhammadiyah Magelang, 2024)
The higher prevalence of stunting in South Sulawesi compared to the national average poses a significant health concern for children, thus necessitating accelerated efforts to reduce stunting. One of the updated strategies for accelerating stunting reduction is the family-centered approach through mentoring families at risk of stunting via the formation of Family Mentor Teams (TPK). Therefore, the objective of this community service is to enhance the role of TPKs by providing comprehensive training on the handling and prevention of stunting from pre-conception to children aged 0-59 months. The implementation method utilizes community-based participatory research (CBPR). The activity was attended by 139 TPKs from 12 districts. The results of the activity demonstrate the effectiveness of the training, as evidenced by an increase in participants' knowledge scores in the post-test (12.96 ± 1.44) compared to the pre-test scores (11.12 ± 1.73).